2017
DOI: 10.4103/pm.pm_395_16
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antiproliferative activities of various solvent fractions from Clerodendrum viscosum leaves

Abstract: Background:Free radicals such as reactive oxygen and nitrogen species, generated in the body, play an important role in the fulfillment of various physiological functions but their imbalance in the body lead to cellular injury and various clinical disorders such as cancer, neurodegenaration, and inflammation.Objective:The objective of this study is to fight this problem, natural antioxidant from plants can be considered as possible protective agents against various diseases such as cancer which might also modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Hydrolysation and absorption of ellagitannins occurs in the small intestine, under a slightly basic or natural pH, which enables further absorption of free EA. EA is then absorbed across the gut epithelium through passive diffusion [17,124]. Unabsorbed free EA and ellagitannins are further metabolized and absorbed in the later part of the gastrointestinal tract.…”
Section: Ellagic Acid Metabolitesmentioning
confidence: 99%
“…Hydrolysation and absorption of ellagitannins occurs in the small intestine, under a slightly basic or natural pH, which enables further absorption of free EA. EA is then absorbed across the gut epithelium through passive diffusion [17,124]. Unabsorbed free EA and ellagitannins are further metabolized and absorbed in the later part of the gastrointestinal tract.…”
Section: Ellagic Acid Metabolitesmentioning
confidence: 99%
“…The two major bioactive compounds found by Ghosh et al ( 2015 ) are N,N-dimethylglycine and 3-deoxy-d-mannoic lactone previously reported to have immune modulating properties and antibacterial activity (Graber et al 1981 ). In vitro studies have shown apoptotic activity of bioflavonoid apigenin isolated from Clerodendrum leaves (Shendge et al 2017 , 2021a ) and anticancer activity of 70% methanolic extracts (Shendge et al 2021a ). However, there is no information for its potential as tick repellent.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles with Clerodendrum viscosum leaf extract were reported to show antiplasmodium activity (46); however, we observed a low selectivity index for Clerodendrum viscosum, suggesting a potential cytotoxic effect on the host. Previous reports have highlighted the potent anticancer properties of Clerodendrum viscosum, demonstrating inhibition of the cell cycle and induction of apoptosis(47). Consequently, the use of molecules derived from this plant should be approached with caution to avoid potential adverse effects.…”
mentioning
confidence: 99%